1988
DOI: 10.1016/0014-2999(88)90072-6
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic muscarinic receptors mediating inhibition of neurogenic contractions in rabbit vas deferens are of the ganglionic M1-type

Abstract: The present study was designed to further eharaeterize the presynaptie musearlnie M 1 -reeeptor responsible for the inhibition of neuragenie eontraetions in the isolated rabbit vas deferens. Eleetrically induced twiteh eontraetions of this preparation were inhibited by the M 1 -agonist, MeN-A-343, and by some of its analogs: 4-ehloro-phenyl derivative> MeN-A-343 > trans-olefinie analog> cis-olefinie analog. The same rank order of potency was obserVed for these agonists to raise the blood pressure of pithed rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…The affinities obtained at uterine muscarinic receptors of immature guinea-pigs were compared to those determined at M 1 (rabbit vas deferens), M 2 (guinea-pig atria) and M 3 receptors (guinea-pig ileum). The antimuscarinic potencies of the antagonists at Mb M2 and M 3 receptors (pArvalues, Table 1) werein good agreement with their affinity estimates determined in radioligand binding studies (Lazareno and Roberts 1989;Waelbroeck et al 1989) and previous functional studies (Barlow et al 1976;Gilani and Cobbin 1986;Micheletti et al 1987;Eltze 1988;Eltze et al 1988;Waelbroeck et al 1989;. A comparison of these affinity values with those determined at uterine muscarinic receptors suggests that the muscarinic receptor mediating contractions of the guinea-pig uterus is pharmacologically unique ( Table 1 ).…”
Section: Discussionsupporting
confidence: 80%
“…The affinities obtained at uterine muscarinic receptors of immature guinea-pigs were compared to those determined at M 1 (rabbit vas deferens), M 2 (guinea-pig atria) and M 3 receptors (guinea-pig ileum). The antimuscarinic potencies of the antagonists at Mb M2 and M 3 receptors (pArvalues, Table 1) werein good agreement with their affinity estimates determined in radioligand binding studies (Lazareno and Roberts 1989;Waelbroeck et al 1989) and previous functional studies (Barlow et al 1976;Gilani and Cobbin 1986;Micheletti et al 1987;Eltze 1988;Eltze et al 1988;Waelbroeck et al 1989;. A comparison of these affinity values with those determined at uterine muscarinic receptors suggests that the muscarinic receptor mediating contractions of the guinea-pig uterus is pharmacologically unique ( Table 1 ).…”
Section: Discussionsupporting
confidence: 80%
“…Eglen and Whiting, 1986;Mitchelson, 1988;Mutschier et al, 1988). M 1 -receptors are found in high density in neuronal tissues such as autonotnie ganglia, cerebral cortex.…”
Section: Lntroductionmentioning
confidence: 99%
“…2) was discovered in the course of structure-activity (selectivity) relationship studies of a series of difenidol and sila-difenidol analogues ( fig. 1) (for recent reviews, see Tacke and Becker, 1987;Mutschier et al, 1988). Structurally, these molecules consist of a central carbinol (silanol) carbon (silicon) atom carrying an OH group, two ring systems and an aminoalkyl group [(CH 2 ) 0 -NR 2 ] (figs.…”
Section: Lntroductionmentioning
confidence: 99%
“…At least three different muscarinic receptor subtypes have been proposed on the basis of different affinities for antagonists such as pirenzepine (Hammer and Giachetti, 1982), methoctramine (Melchiorre, 1988;Melchiorre et al, 1987), AF-DX 116 (Micheletti et al, 1987) and bexahydro-sila-difenidol as weil as sila-hexocyclium (SiHC; Lambrecht et al, 1988;Eltze et al, 1988;Waelbroeck et al, in press). The subtypes have been termed M 1 (neuronal type), M 2 (M 2 a; cardiac type) and M 3 (M 2 p smooth musclejglandular type) receptors (for recent reviews see Mitchelson, 1988;Melchiorre, 1988;Mutschier et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The subtypes have been termed M 1 (neuronal type), M 2 (M 2 a; cardiac type) and M 3 (M 2 p smooth musclejglandular type) receptors (for recent reviews see Mitchelson, 1988;Melchiorre, 1988;Mutschier et al, 1988). Five receptor subtypes were identified by molecular cloning studies and were found to be the products of distinct genes.…”
Section: Introductionmentioning
confidence: 99%